Atomic and Electronic Structures of Interfaces in Dye‐Sensitized, Nanostructured Solar Cells. Issue 6 (1st April 2014) - Johansson, Erik M. J.; Lindblad, Rebecka; Siegbahn, Hans; Hagfeldt, Anders; Rensmo, Håkan
Abstract Key processes in nanostructured dye‐sensitized solar cells occur at material interfaces containing, for example, oxides, dye molecules, and hole conductors. A detailed understanding of interfacial properties is therefore important for new developments and device optimization. The implementation of X‐ray‐based spectroscopic methods for atomic‐level understanding of such properties is reviewed. Specifically, the use of the chemical and element sensitivity of photoelectron spectroscopy, hard X‐ray photoelectron spectroscopy, and resonant photoelectron spectroscopy for investigating interfacial molecular and electronic properties are described; examples include energy matching, binding configurations, and molecular orbital composition. Finally, results from the complete oxide/dye/hole‐conductor systems are shown and demonstrate how the assembly itself can affect the molecular and electronic structure of the materials.